2016
DOI: 10.1016/j.jmau.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylorichronic gastritis updated Sydney grading in relation to endoscopic findings and H. pylori IgG antibody: diagnostic methods

Abstract: Helicobacter pylori (Hp) inhabits the stomach of > 50% of humans and has been established as a major etiological factor in the pathogenesis of chronic gastritis, gastric atrophy, peptic ulcer disease, gastric adenocarcinoma, and gastric mucosa-associated lymphoid tissue lymphoma. The aim of this study was to provide unequivocal information about Hp-associated gastritis grading according to the Sydney grading system and to compare the histopathological features with the endoscopic findings and anti-Hp immunoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 48 publications
1
35
2
2
Order By: Relevance
“…In the case of gastric biopsies 113 as per the present study 104 (92%) were non neoplastic and only 9 (8%) cases were neoplastic, which is similar to that of the study result of Syed Imtiyaz et al [32] report showed that 57.4% of cases were non neoplastic and 42.6% were neoplastic. In the present study, among the non-neoplastic lesions it was observed that chronic superficial gastritis, 24 common neoplastic lesion were adenocarcinoma which correlated with the present study report.…”
Section: Total 113 100supporting
confidence: 92%
See 1 more Smart Citation
“…In the case of gastric biopsies 113 as per the present study 104 (92%) were non neoplastic and only 9 (8%) cases were neoplastic, which is similar to that of the study result of Syed Imtiyaz et al [32] report showed that 57.4% of cases were non neoplastic and 42.6% were neoplastic. In the present study, among the non-neoplastic lesions it was observed that chronic superficial gastritis, 24 common neoplastic lesion were adenocarcinoma which correlated with the present study report.…”
Section: Total 113 100supporting
confidence: 92%
“…However still non-standard histological reporting formats are widely used for gastritis which make it difficult to identify the patients for clinico-endoscopic surveillance. Additionally, there is no validated test to quantify the density of H. Pylori infection [24].…”
Section: Total 113 100mentioning
confidence: 99%
“…We know, that in countries like ours, the H. pylori infection is frequently acquired in childhood and most of the time the disease will develop in adulthood. Early childhood infection typically results in an extended length of infection and likely affords more opportunities for oncogenic mutations [39,40]. Therefore, we believe that vapD presence in H. pylori strains could be a genetic marker for chronicity.…”
Section: Discussionmentioning
confidence: 96%
“…There are scarce literature data regarding immunoreactivity to 50kDa antigen. Seroreactivity to 50kDa antigen was significantly more frequent in infected persons with H. pylori than in noninfected ones 31 , in H. pylori line Hpu24 in GCA than in GU ulcer, but it was not the case with line NCT11 and Hcp29 32 . In a study from Turkey, serum antibodies to 50 kDa antigen were not different between GCA patients and patients without cancer 27 .…”
Section: Discussionmentioning
confidence: 83%